History of Science: Its Role at School and its Place in Biology Textbooks - Hájková, Jana (Scientia in educatione, 2017)
The article is based on an old idea that teaching history of science could improve pupils’ scientific literacy. Since science teachers are usually not familiar with the history of science, they rely on textbooks. This research focused on historical content in Czech textbooks and made use of an instrument tested already on Portuguese physics textbooks. The research project analyzed biology textbooks for secondary school produced by three different publishers (Scientia, Fortuna, Olomouc). The results indicated substantial differences between the textbooks as far as history was concerned. Most of the textbooks under scrutiny mentioned the history of biology only briefly and they usually tended to the so-called Whig view of history.